Regulation of the sintering trajectory of Ho,Pr:Y2O3 ceramics for 2.9 μm mid-infrared lasers by atmospheric sintering - Qing Li; Fei Liang; Jun Wang; Yan Ling Xue; Jie Ma; Peng Liu; Shiyu Sun; Zhan Hui; Jian Zhang; Changhua Zhang; Lili Hu; Haohai Yu; et al. (Journal of Advanced Ceramics)
The sintering trajectory of the Ho,Pr:Y2O3 ceramics could be effectively adjusted by sintering in a flowing oxygen atmosphere instead of vacuum. The final-stage grain growth was significantly suppressed by the use of oxygen atmosphere presintering, resulting in smaller average grain sizes than those of samples sintered under vacuum, while the same relative density was achieved. After hot isostatic pressing (HIP), the oxygen presintered Ho,Pr:Y2O3 ceramics achieved excellent optical quality, with transmittance exceeding 80% at a wavelength of 680 nm. The codoping of Pr3+ as deactivating ions effectively depopulated the lower energy level 5I7 during the Ho3+:5I6 → 5I7 transition, thereby making the Ho,Pr:Y2O3 ceramics more conducive to promoting population inversion in the 2.9 μm laser wavelength range.